Respuesta :
4x = -36
x = -36/4
x = - 9
================
5x - 15 = 50
5x = 50 + 15
5x = 65
x = 65/5
x = 13
================
4(x + 2) - 17 = 35
4x + 8 = 35 + 17
4x = 44
x = 44/4
x = 11
=================
6x + 12 = 4x - 18
6x - 4x = -18 - 12
2x = - 30
x = -30/2
x = -15
==================
1/2(4x - 10) + 5 = x - 11
2x - 5 + 5 = x - 11
2x - x = -11
x = -11
=================
Have a good day :)
x = -36/4
x = - 9
================
5x - 15 = 50
5x = 50 + 15
5x = 65
x = 65/5
x = 13
================
4(x + 2) - 17 = 35
4x + 8 = 35 + 17
4x = 44
x = 44/4
x = 11
=================
6x + 12 = 4x - 18
6x - 4x = -18 - 12
2x = - 30
x = -30/2
x = -15
==================
1/2(4x - 10) + 5 = x - 11
2x - 5 + 5 = x - 11
2x - x = -11
x = -11
=================
Have a good day :)